Parker Pillsbury : Radical Abolitionist, Male Feminist - Robertson, Stacey M. (Book collections on Project MUSE., 2000)
Parker Pillsbury-one of the most important and least examined antislavery activists of the nineteenth century-was a man of intense contradictions. Was he a disruptive eccentric who lashed out at authority (proclaiming Lincoln the worst president in the nation's history) or a sensitive visionary committed to social justice? In the first full-length biography of this remarkable American, Stacey M. Robertson depicts a man who became a leading voice in the antebellum period. Crisscrossing the North for twenty-five years, Pillsbury denounced slavery to all who would listen. In his travels, he often endured the violent rage of mob opposition, but he also received the passionate support of fellow advocates. Robertson's vivid portrayal of this itinerant agitator revises standard views of the antislavery movement by highlighting the interplay between activists such as Pillsbury and the national leadership, which they often challenged. She also reveals how Pillsbury-one of the nation's first male feminists-struggled to reject the notion of male dominance in his political philosophy, public activism, and personal relationships.The biography of a man devoted to justice and equality, this book places his motivations and experiences in the context of nineteenth-century social reform but never strays far from Pillsbury himself. His voice-irascible and fiery, whimsical and compassionate-offers a vivid reminder that history is the story of individual lives.